2009
DOI: 10.1002/clen.200800104
|View full text |Cite
|
Sign up to set email alerts
|

New Attempt to Reduce the Harm of Smoking: Reducing the Nitrosamines Level in Tobacco Smoke by Microwave Irradiation

Abstract: In order to protect the environment and public health, microwave irradiation was investigated as a means of reducing the nitrosamines level of tobacco smoke under mild conditions where the microwave energy was 1 kW and the irradiation time was shorter than 2 min. The microwave-induced elimination of nitrosamines such as Nnitrosopyrrolidine (NPYR) and N-nitrosodiphenylamine (NDPA) was investigated and the impact of the presence of water and salt in the medium on the reduction was assessed in detail. The existen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Up to one-third of the N-nitrosodiphenylamine sorbed (from dichloromethane solution) on mesoporous siliceous SBA-15 containing 10% CuO degraded after being irradiated by 1000 W microwave for 45 s (Xu et al, 2008). Irradiation of cigarettes sealed in its packaging by microwave (1000 W) for 90 s reduced the contents of nitrosamines in the tobacco and mainstream smoke by 25e30 and 50e60%, respectively (Gao et al, 2009). Nonetheless, no previous study has investigated the destruction of NDMA or other nitrosamines sorbed in the micropores of microwave-transparent mineral sorbents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to one-third of the N-nitrosodiphenylamine sorbed (from dichloromethane solution) on mesoporous siliceous SBA-15 containing 10% CuO degraded after being irradiated by 1000 W microwave for 45 s (Xu et al, 2008). Irradiation of cigarettes sealed in its packaging by microwave (1000 W) for 90 s reduced the contents of nitrosamines in the tobacco and mainstream smoke by 25e30 and 50e60%, respectively (Gao et al, 2009). Nonetheless, no previous study has investigated the destruction of NDMA or other nitrosamines sorbed in the micropores of microwave-transparent mineral sorbents.…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies on mitigating the risk of nitrosamines in tobacco and tobacco smoke have shown that these compounds could be decomposed by microwave treatment (Xu et al, 2008;Gao et al, 2009). Up to one-third of the N-nitrosodiphenylamine sorbed (from dichloromethane solution) on mesoporous siliceous SBA-15 containing 10% CuO degraded after being irradiated by 1000 W microwave for 45 s (Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%